2003
DOI: 10.1128/aem.69.10.5941-5949.2003
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Acyl-Homoserine Lactone Quorum Signals for Growth by a Soil Pseudomonad and Pseudomonas aeruginosa PAO1

Abstract: Acyl-homoserine lactones (AHLs) are employed by several Proteobacteria as quorum-sensing signals. Past studies have established that these compounds are subject to biochemical decay and can be used as growth nutrients. Here we describe the isolation of a soil bacterium, Pseudomonas strain PAI-A, that degrades 3-oxododecanoyl-homoserine lactone (3OC12HSL) and other long-acyl, but not short-acyl, AHLs as sole energy sources for growth. The small-subunit rRNA gene from strain PAI-A was 98.4% identical to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
310
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 310 publications
(323 citation statements)
references
References 47 publications
9
310
1
3
Order By: Relevance
“…Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp. (46), and these bacteria were later confirmed to also possess AHL acylase activity (42,44,45,47,51,52). Biochemical analysis of the fate of 3OC10HSL incubated with purified AiiD protein confirmed that AiiD functions as an AHL acylase, releasing HSL and 3-oxodecanoic acid as the major degradation products (46).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 92%
See 4 more Smart Citations
“…Interestingly, homologues of AiiD were also found in various other Ralstonia and Pseudomonas spp. (46), and these bacteria were later confirmed to also possess AHL acylase activity (42,44,45,47,51,52). Biochemical analysis of the fate of 3OC10HSL incubated with purified AiiD protein confirmed that AiiD functions as an AHL acylase, releasing HSL and 3-oxodecanoic acid as the major degradation products (46).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 92%
“…The first gammaproteobacteria reported to have AHL aclyase activity were the soil Pseudomonas isolate PAI-A and P. aerguinosa PAO1, both of which were shown to be able to utilize AHLs with acyl chains of at least 8 carbons for growth, although with differing kinetics (42). Sequence analysis revealed that the P. aeruginosa PAO1 genome encodes four homologues predicted to belong to the Ntn hydrolase superfamily, and thus far three of these (PvdQ, QuiP, and HacB) have been functionally characterized (43).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
See 3 more Smart Citations